RANCANG BANGUN MESIN PENGUPAS KULIT TALAS (Colocasia esculenta L.) - Wahyu Kristian Sugandi; Asep Yusuf; Totok Herwanto; M. Dedi Ardana (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
Taro (Colocasia Esculenta L.,) is one of the leading horticultural commodities in Sumedang District after cassava and sweet potato. According to Department of Agriculture Sumedang District (2015), the quantity of taro semir production is about 2,774 tons per year with harvested area of 243 ha. One of the taro producing area in Sumedang District is in Sukawening, Gorowong Village, Ganeas Subdistrict, Sumedang District. In the era of globalization nowadays, the development of technology helps many people on facilitating the work, so that high work efficiency can be obtained. Beside to fulfill the needs, the emersion of new discovery is encouraged by the limitation of human labor, as traditional way has been commonly applied. To overcome this situation, the production of appropriate technology is recommended to increase efficiency and effectiveness level. This research aimed to design taro peeling machine to accelerate the process of stripping and facilitate the process of slicing or flouring. The research method was engineering. The result showed that the taro peeling machine could peel taro of 22 kg/hour, with dimension of 750 mm length, 600 mm width, and 1060 mm height. The result of the functional test showed that the designed taro peeling machine could work well.